Implementing Journalistic Competence in Realizing Press Professionalism in Riau Province - Eka Putra (Ikatan Sarjana Komunikasi Indonesia, 2024)
To ensure professionalism, every journalist must fulfil one important factor called journalistic competence. Journalistic competence is assessed through three main aspects: awareness, knowledge and skills. Competent journalists should be able to produce quality journalistic works Â and support the realisation of press professionalism. This study aims to determine journalists' understanding of journalist competence and enable them to apply competence values in the field. This research was conducted in Riau Province, Indonesia, using a qualitative method with purposive sampling technique. Six journalists, consisting of three competency-certified and three non-competency-certified journalists, were interviewed in depth. From the data obtained, the research was followed by a Focus Group Discussion (FGD) with eleven research participants to assess the application of journalists' competencies and the social responsibility of the press. The FGDs generated several views on the existence of journalists and discussed solutions to problems faced by journalists and media companies in Riau. This study has three outcomes: understanding of journalists' competencies, the application of journalists' competencies and social responsibility, and community involvement in realising press professionalism. This study concludes that every journalist still needs to improve their professionalismÂ by understanding and applying the values of journalist competence. This research gave birth to a new concept of community involvement in promoting press professionalism supported by Press Law Number 40 of 1999.